Leper Kings - Badger, Cormac (Kansas State University, 2016)
This project is the first portion of the novel Leper Kings. Frank Nash, a bank robber and historical figure from the jazz age Midwest, is struggling to launch his criminal career and find his place in history. A series of his confidants and cronies records his attempts to gain money and notoriety through violence, only to find that Nash has the uncanny ability to propel them forward through time and into visions of the American future through a carefully manipulated series of robberies, assaults, and murders. Nash, aware that he is destined to die in the Kansas City Union Station Massacre of 1933, desperately seeks ways to launch his associates Lucas Mooney and Vernon Miller further into the future, beyond Nash’s death, to experience and catalogue violent events that press increasingly into our present age. As their methods of soothsaying become gradually more reprehensible, Miller and Mooney question their chrono-magical project and find that their volatile leader and prophet, Frank Nash, is slowly and steadily losing his hold on the present reality and those in it.
Keywords: Creative writing